Community involvement of seniors in the Eastern Townships - Gosselin, Chedly; Viens, Caroline (Journal of Eastern Townships Studies, 2006)
This paper explores Anglophone seniors' participation within the community of the Estrie region of Quebec. A healthy relationship between Anglophone and Francophone communities improves access to state health and social services and relieves the social isolation of those living in rural areas. Immigrant migration to the area as well as out-migration of young Anglophones is profoundly affecting the delivery of health and social services as well as changing family, community, nation, culture and what it means to be a citizen.

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

The network’s approaches for the maintenance and creation of primary health services in English for the Quebec City region - Sanderson, Duncan; Grégoire, Louise; Reinharz, Daniel (Agence de la santé et des services sociaux de la Capitale-Nationale & Direction régionale de santé publique, 2006)